Cover Crop Effects on Corn in a Corn/Soybean Rotation - D. E. Shoup; I. A. Ciampitti; J. Kimball; Gretchen Sassenrath (Kansas Agricultural Experiment Station Research Reports, 2017)
A research study was established in 2013 in a corn and soybean rotation with cover crops planted soon after each crop harvest. A variety of complex cover crop mixtures were evaluated ranging from single-specie to 7-specie mixtures. Cover crops were terminated in the spring prior to corn planting. Corn yield responded differently among the three years of the study. In general, 2014 and 2016 showed a similar trend of decreased corn yield as the complexity of cover crop specie mixtures increased. Significant corn yield losses ranged from 8.6 to 15.1 bu/a across all cover crop treatments in 2014. In 2016, corn yield loss was 8.1, 9.7, and 12.0 bu/a for the 3-specie mix, rye, and 7-specie mix, respectively. In 2015, however, an opposite trend was observed in the trial with increasing corn yield across all cover crop treatments. A dry fall following soybean harvest resulted in poor germination of all cover crops, so no biomass accumulated prior to corn planting. Corn yield increases ranged from 10.5 to 16.4 bu/a in 2015.
Keywords: cover crop; corn; rye; radish